Thermoablative Techniques for Excessive Central Airway Collapse: An Ex Vivo Pilot Study on Sheep Tracheal Tissue. Issue 3 (July 2020) - de Lima, Andres; Vidal, Barbara; Kheir, Fayez; VanderLaan, Paul A.; Mallur, Pavan S.; Gangadharan, Sidhu P.; Majid, Adnan
Abstract : Background: Tracheobronchoplasty is the definitive treatment for patients with symptomatic excessive central airway collapse. This procedure is associated with high morbidity and mortality rates. Bronchoscopic techniques are an appealing alternative with less morbidity and the ability to apply it in nonsurgical patients. Although thermoablative methods have been proposed as treatment options to induce fibrosis of the posterior tracheobronchial wall, no studies have compared direct histologic effects of such methods. This study compared the effects of electrocautery, radiofrequency ablation, potassium titanyl phosphate laser, and argon plasma coagulation (APC) in the tracheobronchial tree in an ex vivo animal model. Methods: Four adult sheep cadavers were used for this study. Under flexible bronchoscopy, the posterior tracheal membrane was treated using different power settings on 4 devices. The airways were assessed for the presence of treatment-related histopathologic changes. Results: Histologic changes observed were that of acute thermal injury including: surface epithelium ablation, collagen fiber condensation, smooth muscle cytoplasm condensation, and chondrocyte pyknosis. No distinct histologic differences in the treated areas among different modalities and treatment effects were observed. APC at higher power settings was the only modality that produced consistent and homogenous thermal injury effects across all tissue layers with no evidence of complete erosion. Conclusion: Although electrocautery, radiofrequency ablation, potassium titanyl phosphate laser, and APC all induce thermal injury of the airway wall, only APC at high power settings achieves this effect without complete tissue erosion, favoring potential regeneration and fibrosis. Live animal studies are now plausible.